2021
DOI: 10.1002/wat2.1552
|View full text |Cite
|
Sign up to set email alerts
|

Water security in sub‐Saharan Africa: Understanding the status of sustainable development goal 6

Abstract: The world is nearing the 2030 target‐year by which sustainable development goals (SDGs) should be achieved. While other developing regions seem to be making progress toward achieving SDG6, sub‐Saharan Africa (SSA) is lagging behind significantly, particularly with regard to access to water supply and sanitation (WSS). As a result, most studies evaluating progress toward the achievement of water security SDGs in SSA have focused on WSS while the rest of the SDG6 targets have received scant attention, often usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 162 publications
(191 reference statements)
1
15
1
Order By: Relevance
“…Our results also indicated that population-driven water scarcity is more apparent in the urban areas with a high-population density than in districts with a low-population density. These findings are in line with recent calls to identify the factors driving water scarcity at the local scale in Africa (Nkiaka et al 2021a).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our results also indicated that population-driven water scarcity is more apparent in the urban areas with a high-population density than in districts with a low-population density. These findings are in line with recent calls to identify the factors driving water scarcity at the local scale in Africa (Nkiaka et al 2021a).…”
Section: Discussionsupporting
confidence: 90%
“…Therefore, the objectives of this study are to (1) conduct a spatiotemporal trend analysis of precipitation and temperature across all districts in Anglophone Cameroon; (2) combine the water balance and water footprint concepts and satellite observations to estimate water availability across all districts in Anglophone Cameroon; and (3) assess demand-driven water scarcity in terms of blue and green water scarcities and population-driven water scarcity quantified using the Falkenmark index. The objectives of this study are in line with recent calls to identify water scarcity hotspots at the local scale to support effective decision-making (Quinteiro et al 2019;Nkiaka et al 2021a).…”
Section: Introductionmentioning
confidence: 79%
“…In the context of irrigation development, this means using water quality monitoring data to update the knowledge of nutrient water pollution risk so that remedy actions, if needed, can be taken in a timely manner. Most countries in Sub-Saharan Africa lack sufficient capacity to monitor water quality (Peletz et al 2016, Nkiaka et al 2021, investment is needed to strengthen the capacity of water quality monitoring in the region. At implementation level, making effective environmental investment in improved improve land management and enhancing water quality monitoring capacity may involve efforts of building appropriate institutions to incentivize farmers' adoption of land management practices and to improve performance of water monitoring programs (Drechsel et al 2005, Peletz et al 2018, Pandey 2019, exploring the application of new low-cost water quality monitoring technologies (Dube et al 2015, Pellerin et al 2016, and developing decision support systems to facilitate selection placement of land management practices for nutrient water pollution control (Yang and Best 2015, Dai et al 2018.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…For example, there are only a few case studies reporting on the use of these products in the upper Blue Nile River basin (Koukoula et al, 2020;Lakew et al, 2020) and the Zambezi River basin (Gründemann et al, 2018). Considering the scale of water insecurity in Africa, compounded by acute data scarcity (Nkiaka et al, 2021), we feel that evaluating the performance of gridded WRR products in Africa may enhance their adoption in water management in the region. On the other hand, several studies evaluating the performance of gridded data in Africa have focused mostly on precipitation (Dinku et al, 2018;Satgé et al, 2020) while few studies that have evaluated gridded ET products focused on large basins (Blatchford et al, 2020;Weerasinghe et al, 2020;McNamara et al, 2021), and mostly adopted an annual timescale.…”
Section: Introductionmentioning
confidence: 99%